2019
DOI: 10.1002/adom.201901679
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Spacer Cation Stabilization of Blue‐Emitting n = 2 Ruddlesden–Popper Organic–Inorganic Halide Perovskite Films

Abstract: Ruddlesden–Popper halide perovskite (RPP) materials are of significant interest for light‐emitting devices since their emission wavelength can be controlled by tuning the number of layers n, resulting in improved spectral stability compared to mixed halide devices. However, RPP films typically contain phases with different n, and the low n phases tend to be unstable upon exposure to humidity, irradiation, and/or elevated temperature which hinders the achievement of pure blue emission from n = 2 films. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 59 publications
0
62
0
Order By: Relevance
“…Substantial efforts have been made in the past several years to obtain blue perovskite emitters, such as perovskite nanocrystals (NCs), [ 19–25 ] 2D perovskite nanoplatelets, [ 26–32 ] and quasi‐2D perovskites. [ 33–39 ] In particular, the quasi‐2D perovskites are rising as efficient luminescent materials for highly performed blue PeLEDs due to the cascade energy landscape for efficient exciton transfer and the subsequent radiative recombination. Typically, the quasi‐2D perovskites have a formula of B 2 (APbBr 3 ) n −1 PbBr 4 , where B is an organic spacer cation, A is a monovalent cation (e.g., Cs + , methylammonium (MA + ) or formamidinium, (FA + )), and n represents the number of lead halide octahedral layers.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Substantial efforts have been made in the past several years to obtain blue perovskite emitters, such as perovskite nanocrystals (NCs), [ 19–25 ] 2D perovskite nanoplatelets, [ 26–32 ] and quasi‐2D perovskites. [ 33–39 ] In particular, the quasi‐2D perovskites are rising as efficient luminescent materials for highly performed blue PeLEDs due to the cascade energy landscape for efficient exciton transfer and the subsequent radiative recombination. Typically, the quasi‐2D perovskites have a formula of B 2 (APbBr 3 ) n −1 PbBr 4 , where B is an organic spacer cation, A is a monovalent cation (e.g., Cs + , methylammonium (MA + ) or formamidinium, (FA + )), and n represents the number of lead halide octahedral layers.…”
Section: Figurementioning
confidence: 99%
“…[42] Jin et al reported utilization of phenylbutylamine bromide (PBABr) as the spacer cation to construct PBABr y (Cs 0.7 FA 0.3 PbBr 3 ) with perovskite nanoparticles (NPs) embedded in quasi-2D phases, and obtained an EQE of 9.5% and lifetime of 250 s for the blue PeLEDs. [43] In addition, the joint organic cations, such as PEABr and butylammonium bromide (BABr), [34] PEABr and propylammonium bromide (PABr), [44] PEABr and iso-propylammonium bromide (IPABr), [39,45] and 1,4-Bis(aminomethyl) benzene bromide (P-PDABr 2 ) and PEABr [46] were also employed as the spacer cations to modulate the quasi-2D perovskite phase distribution for high phase purity and thus efficient light emission. Besides optimizing the organic spacer cations in quasi-2D perovskites, the composition of "A-site" has been also tuned to prolong PeLED operational stability, such as rubidium-cesium alloyed quasi-2D PEA 2 (Rb x Cs 1−x ) n−1 PbnBr 3n+1 perovskite, [47] and mixture of monovalent cation perovskite (e.g., PEA 2 (Cs/Rb/ FA/K)Pb n (Cl/Br) 3n+1 [48] ).…”
mentioning
confidence: 99%
“…[18][19][20][21] The demand for UV photodetection is currently increasing in various fields, such as medical science, civilian and defense regions, biological detection, UV astronomy, and endoatmospheric sensing. [22][23][24][25][26][27][28] Combining Al plasmonics with GaN is an excellent method for various applications, such as ultrahigh responsivity, detectivity, and visible blind photodetection. Recently, Ahmadivand et al theoretically demonstrated the use of Al oligomers on GaN for ultraviolet photodetection; [29] however, experimental studies of Al plasmonics with GaN have not been performed.…”
Section: Doi: 101002/advs202002274mentioning
confidence: 99%
“…[18] Most noteworthy, previous literature in the field already pointed out the importance of structural dynamics and local distortions in affecting the electronic features of hybrid halide perovskites, as related, for instance, to the variation of the optical properties with temperature, [36] as first step toward the formation of point defects, [37] to explain less effective electron-phonon scattering events. [38] We now turn to the collective electrostatic effects of the cations on the energy of the frontier crystalline orbitals. In 2D slabs, an extended monolayer of oriented dipoles produces a jump (ΔE) in electrostatic potential with respect to vacuum, which can be cast in terms of the component of the dipole moment orthogonal to the slab surface (μ z ) per unit area (A) via the Helmholtz relation (1) (where ε 0 is the vacuum dielectric constant).…”
Section: Computational Investigationmentioning
confidence: 99%